Initial development of Eucalyptus grandis x E. urophylla plants when inoculated with Pisolithus spp. from Pinus spp. colonizations - Barretto, Vitor Corrêa de Mattos; Barretto, Flávia Risse de Mattos; Gonçalves, Lucas Emanuel Nunes; Peixoto, Gustavo Henrique Silva; Lima, Milton Luiz da Paz; Carvalho, Daniel Diego Costa (Revista Ecologia e Nutrição Florestal - ENFLO, 2018)
Mycorrhization is a practice whose main abenefits are summarized in the optimization of the use of nutrients and water by the plant. Therefore, this study aimed to measure the initial development of Eucalyptus grandis W. (Hill ex Maiden) x E. urophylla S.T. Blake plants when inoculated with Pisolithus spp. using chemical and organic fertilizer. Mychorrhiza inocula were obtained from Pinus sp. local stands and the inoculation was carried out in eucalyptus at 107 days old. At 90 days after inoculation, it was measured shoot height (SH), stem diameter (SD), shoot dry matter (SDM), root dry matter (RDM) and roots colonization. The design was completely randomized (CRD), with three treatments: soil with simple superphosphate (40 mg L-1), soil with poultry litter (1.0 g L-1) and control, which were submitted or not to the mycorrhiza effects. There was not difference between plants with and without mychorriza, except the treatment that did not use mychorriza with poultry litter for RDM, which was superior than using mychorriza. The better mycorrhization percentage were found in simple superphosphate treated plants. The inoculation by Pisolithus spp. does not make influence on eucalyptus plants development under greenhouse conditions.